NILAI EKONOMI AIR BUANGAN AC (AIR CONDITIONER) SEBAGAI SUMBER ALTERNATIF UNTUK PEMENUHAN KEBUTUHAN AIR DI KANTOR PEMERINTAHAN KABUPATEN BOGOR - Benny Osta Nababan; Yesi Dewita Sari; Mujito Mujito; Rini Kusumawati; Mutiara Saripah; Silma Mausuli; Rusli Dwianto; I Gusti Ayu Darma Cintia (Institut Teknologi dan Bisnis Dewantara, 2023)
Reusing AC wastewater is a potentially limited water resource. This research aims to: determine the quality of AC wastewater, estimate the availability of AC wastewater in Bogor Regency government offices, and analyze the economic value of the availability of AC wastewater in Bogor Regency Government Offices. The method used in this research is a technical analysis of water quality tests, quantitative descriptive tabulation calculations to obtain the amount of AC wastewater in each SKPD, and WTP (Willingness To Pay). This research shows that AC wastewater can be used as a water resource because the raw water parameters are good for household purposes such as for toilet use, cleaning services, watering plants, and washing. The estimated AC wastewater produced by 33 SKPDs of the Bogor Regency Government in 1 year is 4,118,400 liters. Water requirements by employees for 1 year are 25,877,601.30 liters. In this case, if AC wastewater can be used, it will cover 15.91% of employee water needs in 1 year. The economic value of AC wastewater is IDR 3.57/liter. If multiplied by the amount of AC wastewater that has not been utilized, the total value of AC wastewater in 1 year is IDR 14,702,688.00. The value of AC wastewater is only 44.6% of the PDAM price per liter. This value is still low because AC waste water is known as waste.